Alterations in the Interplay between Neurons, Astrocytes and Microglia in the Rat Dentate Gyrus in Experimental Models of Neurodegeneration - Lana, Daniele; Ugolini, Filippo; Nosi, Daniele; Wenk, Gary L.; Giovannini, Maria G. (Frontiers in Aging Neuroscience, 2017)
The hippocampus is negatively affected by aging and neurodegenerative diseases leading to impaired learning and memory abilities. A diverse series of progressive modifications in the intercellular communication among neurons, astrocytes and microglia occur in the hippocampus during aging or inflammation. A detailed understanding of the neurobiological modifications that contribute to hippocampal dysfunction may reveal new targets for therapeutic intervention. The current study focussed on the interplay between neurons and astroglia in the Granule Layer (GL) and the Polymorphic Layer (PL) of the Dentate Gyrus of adult, aged and LPS-treated rats. In GL and PL of aged and LPS-treated rats, astrocytes were less numerous than in adult rats. In GL of LPS-treated rats, astrocytes acquired morphological features of reactive astrocytes, such as longer branches than was observed in adult rats. Total and activated microglia increased in the aged and LPS-treated rats, as compared to adult rats. In the GL of aged and LPS-treated rats many neurons were apoptotic. Neurons decreased significantly in GL and PL of aged but not in rats treated with LPS. In PL of aged and LPS-treated rats many damaged neurons were embraced by microglia cells and were infiltrated by branches of astrocyte, which appeared to be bisecting the cell body, forming triads. Reactive microglia had a scavenging activity of dying neurons, as shown by the presence of neuronal debris within their cytoplasm. The levels of the chemokine fractalkine (CX3CL1) increased in hippocampal homogenates of aged rats and rats treated with LPS, and CX3CL1 immunoreactivity colocalized with activated microglia cells. Here we demonstrated that in the Dentate Gyrus of aged and LPS-treated rats, astrocytes and microglia cooperate and participate in phagocitosis/phagoptosys of apoptotic granular neurons. The differential expression/activation of astroglia and the alteration of their intercommunication may be responsible for the different susceptibility of the DG in comparison to the CA1 and CA3 hippocampal areas to neurodegeneration during aging and inflammation.